Spontaneous Rupture of Splenic Artery Aneurysm during the First Trimester of Pregnancy: Report of an Extremely Rare Case and Review of the Literature. (17th September 2012) - Pavlis, Theodoros; Seretis, Charalampos; Gourgiotis, Stavros; Aravosita, Paraskevi; Mystakelli, Christina; Aloizos, Stavros
Abstract : Splenic artery aneurysm (SAA) occurs predominantly in women and the majority of them are asymptomatic until rupture. In cases of spontaneous rupture of an SAA, maternal and fetal mortality rates remain extremely high. Furthermore, the spontaneous ruptures of SAAs predominantly appear during the third trimester of pregnancy. We present the third known case of spontaneous SAA rupture during the first trimester of pregnancy, which manifested as sudden hypovolemic collapse and was successfully confronted with combined aggressive resuscitation and emergency surgical operation.